Tracing the Interests of Indonesian Khonghucu Adherents, Between Business and Academia - Hadian, Emma Nurmawati; Wakhudin, Wakhudin (PT. Riset Press International, 2023)
This study aims to examine the interests of Indonesian Khonghucu religious adherents, especially related to business and academia. The people of Khonghucu are known to be very good at doing business, so they are generally financially successful. Since obtaining legality since the time of President K.H. Abdurrahman Wahid, Khonghucu has now continued to develop. Among Khonghucu businessmen, are there those who choose to become academics, pursue religion more, and develop Khonghucu? This study used a descriptive qualitative approach with phenomenological methods. The informan was a Khonghucu adherent who had succeeded in becoming a businessman and academic. Data collection techniques are carried out by interviews, observation, and documentation studies. Data validation is done by triangulation, both technique triangulation and source triangulation. The results showed that Khonghucu adherents in Indonesia are very interested in becoming entrepreneurs, although some of them prefer academic careers. Both options are influenced by family culture and values, labor market opportunities and demands, the influence of the educational environment and personal aspirations and abilities of individuals. Those in business contribute to Indonesia's economy, while those who choose academia preserve and pass on Confucian religious traditions to future generations. Both those who choose business and academia recognize that pursuing religion is a valuable devotion for Confucians and Indonesian society as a whole.